Evaluating Outdoor Thermal Comfort Using a Mixed-Method to Improve the Environmental Quality of a University Campus - Nasim Eslamirad; Abel Sepúlveda; Francesco De Luca; Kimmo Sakari Lylykangas (Energies, 2022)
Thermal comfort in cities is increasingly becoming a concern and comfortable places can be highly valuable for a variety of activities. Our investigation aims to explore how to improve the quality of cities by considering the relationship between microclimatic conditions, thermal sensation, and human preferences. The case study conducted in the open areas of Tallinn University of Technology (TalTech) campus, which is quite populated by visitors, staff, and students. We used a mixed-methods approach to assess outdoor thermal comfort, based on qualitative and quantitative findings of the relationships between the measured weather conditions and the results of thermal comfort assessment through the PET index and subjectively perceived thermal sensation. In the qualitative part, data was collected through semi-structured interviews. The main conclusions from the interviews were used to design a survey and the samples. Based on the results, it was possible to identify places that offer different levels of thermal comfort. Thus, the study helps to improve thermal comfort at the campus, which is one of the goals of the Green Transition project to make the campus fully sustainable. Moreover, the methodology is applicable in different urban areas to improve urban health and sustainability and create resilient urban environments.